Tapered CYTOP Optical Fiber for Single Peak FBG Sensor - Woyessa, Getinet Taffesse; Theodosiou, Andreas; Markos, Christos; Kalli, Kyriacos; Bang, Ole (My University, 2022)
We demonstrated a single peak FBG reflection spectrum in multimode perfluorinated polymer optical fiber by tapering the fiber and then inscribing an FBG in the waist section of the taper.
Keywords: Multimode fibers; Plastic optical fibers; FBG sensor; Multimodes; Perfluorinated polymers; Polymer optical fibre; Reflection spectrum; Single peak; Fiber Bragg gratings